Mengatasi Bullying Melalui Pendekatan Behavioristik Dalam Membangun Karakter Kristiani di Lingkungan Sekolah - Sugeng, Tadius Marjuni; Urbanus, Urbanus; Suprihatin, Suprihatin; Saputra, Prilingga (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
Bullying is a form of aggressive behavior that is carried out repeatedly and involves power imbalance, which has a negative impact on students' social and emotional development. In the context of Christian education, this behavior fundamentally contradicts the concept of Christian character, which emphasizes the values of love, respect, and empathy as a tangible manifestation of faith in relationships with others. This study aims to address bullying behavior through a behavioristic approach as an effort to shape Christian character in the school environment. The research method used is a descriptive qualitative approach. The results show that the application of behavioristic techniques such as positive reinforcement, controlled punishment, and prosoccial behavior habituation has been proven to significantly reduce the frequency of bullying. In addition, the application of Christian values in reinforcing positive behavior accelerates the process of internalizing Christian character. A behavioristic approach contextualized with Christian principles can overcome bullying in shaping character in the school environment.